Cells under stress: The mechanical environment shapes inflammasome responses to danger signals. Issue 1 (15th January 2019) - Joshi, Hemant; Morley, Sharon Celeste
Abstract: Many intracellular signals, such as host danger-associated molecules and bacterial toxins during infection, elicit inflammasome activation. However, the mechanical environment in tissues may also influence the sensitivity of various inflammasomes to activation. The cellular mechanical environment is determined by the extracellular tissue stiffness, or its inverse, tissue compliance. Tissue stiffness is sensed by the intracellular cytoskeleton through a process termed mechanotransduction. Thus, extracellular compliance and the intracellular cytoskeleton may regulate the sensitivity of inflammasome activation. Control of proinflammatory signaling by tissue compliance may contribute to the pathogenesis of diseases such as ventilator-induced lung injury during bacterial pneumonia and tissue fibrosis in inflammatory disorders. The responsible signaling cascades in inflammasome activation pathways and mechanotransduction crosstalk are not yet fully understood. This rather different immunomodulatory perspective will be reviewed and open questions discussed here. Graphical Abstract: Review on how the internal cytoskeleton and extracellular compliance modulate inflammasome activation.